On the Road to Biopolymer Aerogels—Dealing with the Solvent - Subrahmanyam, Raman (Gels, 2015)
Aerogels are three-dimensional ultra-light porous structures whose characteristics make them exciting candidates for research, development and commercialization leading to a broad scope of applications ranging from insulation and catalysis to regenerative medicine and pharmaceuticals. Biopolymers have recently entered the aerogel foray. In order to fully realize their potential, progressive strategies dealing with production times and costs reduction must be put in place to facilitate the scale up of aerogel production from lab to commercial scale. The necessity of studying solvent/matrix interactions during solvent exchange and supercritical CO(2) drying is presented in this study using calcium alginate as a model system. Four frameworks, namely (a) solvent selection methodology based on solvent/polymer interaction; (b) concentration gradient influence during solvent exchange; (c) solvent exchange kinetics based on pseudo second order model; and (d) minimum solvent concentration requirements for supercritical CO(2) drying, are suggested that could help assess the role of the solvent in biopolymer aerogel production.